Tick-borne encephalitis: students’ attitude and knowledge analysis - Mineikytė , R.; Navickaitė, G.; Valaikienė , J. (Neurologijos seminarai, 2018)
Background. Lithuania is one of the countries with the highest incidence of TBE in Europe. In 2015 there was 12 cases per 100 000 people per year and in 2016 this number was higher by two times. The aim of this study is to investigate and evaluate I–IV year medical students’ attitude and knowledge of TBE incidences in Lithuania, risk of getting it, complications, treatment, preventive methods and behaviour, and information sources about tick-borne diseases. Materials and methods. The study was conducted using an anonymous questionnaire, which was administered to 404 students studying at I–IV year medical courses (average age 20.7±1.56, range from 17 to 30 years). The questionnaire consisted of 21 semi-closed questions. There were 6 questions about TBE, its incidence, complications and treatment, 9 questions about preventive methods of tick-borne diseases, and 2 questions about information sources and how accessible this information is. Results. TBE as a tick-borne disease was named by 397 (98.3%) students and Lyme borreliosis was named by 382 (94.6%). The fact that TBE incidence in Lithuania is high (>11 cases per 100 000 per year) was known only to 58 (14.4%) respondents, 159 (39.4%) answered that the incidence is medium (2–10 cases per 100 000 per year). The most commonly named complications of TBE were paralysis and paresis – 327 (81%) students. 3 respondents (1%) thought that TBE is a dis ease without any complications. The most effective preventive method, chosen by 237 (58.7%) students, was vaccination. There were 169 (41.8%) vaccinated students. 106 (26%) students thought that there are no specific treatment for TBE, only supportive care. The fact that people are well enough informed about tick-borne diseases was supported by 113 (28%) students, and 193 (47.8%) students thought that there is lack of information. 219 (54%) students named media as the main source of information. Conclusions. Only 14.4% of students knew that TBE incidence in Lithuania is high, not medium. Almost all of them agreed that TBE causes long term complications but only one of four knew that there is no specific, only supportive care. The majority of students think that vaccination is the most effective preventive method and almost half of students were vaccinated against tick-borne encephalitis. Every second student thinks that society is not enough informed about tick-borne diseases.